Effective Hydration-Centered Management of Acute Gastroenteritis in a 13-Year-Old Patient: Insights from Primary Care Practice - Nia Triswanti; Dian Vitria; Syalwa Lutfhi Rahmadini; Shafa Annisa Rembulan E. K; Shevani Adelia; Silviatara Putri Maharani; Siti Aisyah; Siti Rahayu (Biomedical Research and Theory Letters, 2025)
Acute gastroenteritis remains one of the most common acute conditions in children and adolescents, frequently leading to dehydration and requiring prompt clinical assessment to prevent further complications. Although management guidelines are well established, variability in presentation and progression highlights the importance of individualized and holistic diagnostic approaches in primary care. This report describes a case involving a 13-year-old male who presented with severe gastrointestinal symptoms, including diarrhea exceeding ten episodes per day over three consecutive days, more than five episodes of vomiting, abdominal pain, fever, and generalized weakness. Clinical examination demonstrated a weakened overall condition, blood pressure of 100/70 mmHg, pulse 85 beats per minute, respiratory rate 20 breaths per minute, temperature 36.7°C, and signs consistent with mild to moderate dehydration. Laboratory evaluation revealed slightly decreased leukocyte levels, suggesting a likely viral etiology. The management in this case reflects the methodological core of the intervention: a holistic, stepwise approach integrating intravenous rehydration, symptomatic therapy, and adaptive pharmaceutical adjustments based on evolving clinical features. The patient was administered Ringer’s Lactate intravenously through a loading dose followed by controlled infusion at 25 drops per minute. Antiemetic therapy with ondansetron, antipyretics, antacids, attapulgite, and oral rehydration solution were provided initially. On the second day, antibiotics and ranitidine were introduced in response to persistent gastrointestinal complaints and to prevent potential secondary complications. The results demonstrated clear clinical improvement within 72 hours, marked by decreased diarrhea frequency, cessation of vomiting, and normalization of vital signs (blood pressure 100/65 mmHg; pulse 80 beats per minute). Hydration status returned to normal, and no complications or referral indications were identified. This case underscores the conclusion that integrating holistic assessment with tailored rehydration strategies and selective pharmacologic therapy can produce rapid and effective recovery in pediatric acute gastroenteritis. The novelty lies in demonstrating how a dynamic, symptom-guided model of care in a primary health setting can optimize outcomes while minimizing unnecessary escalation of treatment.